The Evaluation of Flow Property of Alginate Impression Material Mixed with Gargle Solutions - Sumadhi Sastrodihardjo; Kholidina Imanda Harahap (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
The effects of antiseptic and gargle solutions mixed with the irreversible hydrocolloid alginate impression material to anti-bacterial activity and several properties had been elucidated. The flow property of the such impression has been not elucidated yet. The aim of the study was to evaluate the flow property of alginate impression mixed with gargle solution. Aroma Fine Plus alginate impression material was used and mixed with aquadest as control and Minosep, Betadine and Total Care gargle solutions. Ratio between alginate and each solutions were performed by following the producer’s guidance as 8.4gr alginate and 20ml solution. The every alginate mixtures were made in triplicate (n=3). Measurement of flow capability was performed by using 0.5ml of alginate mix laid on glass plate covered with cellophane strip and loaded with 1kg metal for 1 minute. The major and minor diameters were measured by using digital caliper. Data were analyzed by using one way ANOVA (α= 0.05). Aroma Fine mixed with aquadest showed the flow capability was about 26.18mm. Mixed with Minosep showed about 27.85mm, with Betadine 29.19mm and Total Care 27.11mm respectively. Statistically show a significant different flow capability between aquadest and Betadine mixed impression (p=0.01). Minosep and Total Care gargle solutions showed insignificant different with aquadest mixed impression (p>0.05). It can be concluded that the utilizing of Minosep and Total care gargle solution as solutions mixed with alginate impression material have no effect to flow property of the impression, except by using Betadine gargle solution.